Mineral Alteration and Fracture Influence on the Elastic Properties of Volcaniclastic Rocks. Issue 5 (22nd May 2019) - Durán, Evert L.; Adam, Ludmila; Wallis, Irene C.; Barnhoorn, Auke
Abstract: In geothermal environments, the physical properties of rocks, such as porosity and alteration, are highly variable and control the reservoir's elastic and hydraulic properties. Elastic wave velocity in volcaniclastic rocks and their relation to fractures, pore shapes, and mineral alteration is mostly unknown. We measure ultrasonic P and S wave speeds on volcanic rocks from the Ngatamariki Geothermal Reservoir, New Zealand. Data clustering of wave speed versus porosity and density allow us to classify lithotypes of variable propylitic and phyllic mineral alteration. Wave speeds increase first due to porosity reduction as a result of mineral alteration and welding and, second, due to the high elasticity of alteration minerals (epidote, chlorite, and carbonates). We model the rock porosity as composed of equant pores and oblate‐spheroidal microfractures following an elastic effective medium model. For our samples, microfracture porosities range from 4% in the volcaniclastic tuffs to less than 1% in the ignimbrites, which we validate with pycnometer porosity data under effective pressure. We quantify that within one geological volcaniclastic formation, wave speeds vary up to 47% due to rock alteration and welding, while the effect of microfractures and changes in effective stress on wave speeds is secondary (up to 11%) but not negligible. From the experimental and numerical results we show that equant pores remain open at reservoir conditions (2, 000 m) and can retain considerable porosity (10%). Our analysis has implications for microfracture and pore network characterization in geothermal reservoirs, in particular, in vapor‐dominated systems where matrix porosity and permeability play a role. Key Points: For our volcaniclastic rocks, propylitic and phyllic alteration as well as welding decrease porosity and increase elastic wave speeds; there is no correlation between rock alteration and sample depth Microfracture porosity is quantitatively estimated from elastic wave effective media models and validated with experimental data Rock alteration and welding in volcaniclastic rocks of similar origin have a larger effect on seismic wave speeds than microfracture porosity alone